2012
DOI: 10.1111/chf.12014
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Management Intervention to Improve Self‐Care and Quality of Life in Heart Failure Patients

Abstract: Self-management intervention is a good method to improve self-care ability, as such, to promote quality of life. However, the research focused on self-management intervention in heart failure patients in Taiwan is very limited. Therefore, the purposes of this study were to test the effectiveness of self-management intervention in patients with heart failure in Taiwan and examine the relationship between self-care ability and quality of life. A quasi-experimental design was used in this study with convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 26 publications
(61 reference statements)
7
59
1
6
Order By: Relevance
“…Evidence to support a link between self-care in patients with HF and health outcomes is limited. [19,54] The results from our study are in line with the results from the study by Tung, et al [19] Furthermore we found a correlation between self-care behavior and reduced anxiety/depression. It has previously been asserted that there is a clear relationship between depression and poor Health Status, a relationship which seems to be associated with poor self-care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Evidence to support a link between self-care in patients with HF and health outcomes is limited. [19,54] The results from our study are in line with the results from the study by Tung, et al [19] Furthermore we found a correlation between self-care behavior and reduced anxiety/depression. It has previously been asserted that there is a clear relationship between depression and poor Health Status, a relationship which seems to be associated with poor self-care.…”
Section: Discussionsupporting
confidence: 92%
“…In general, there is little evidence for the effect of rehabilitation interventions after discharge from outpatient clinics. [19] Worldwide there is a need for developing effective educational interventions [20] as only 20 to 60% of patients with HF [21,22] adhere to advice from health care professionals. No single intervention seems to be effective in increasing adherence and to support patients in making adequate behavioral changes during rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…90 Researchers found that improvement in a patient's selfmanagement could be achieved in a shorter period of time than improvement in adherence to activities to maintain physiological stability (ie, self-care maintenance). 67,92 For example, in the study by Caldwell et al, 67 self-care maintenance behaviors (eg, daily weight monitoring) were enhanced at 3 months in the intervention group compared with usual care, but not self-care management behaviors (eg, calling providers when HF symptoms worsened). In 2 studies in which symptom occurrence was measured, patients in the intervention group experienced fewer symptoms than with usual care.…”
Section: Hf Outcomesmentioning
confidence: 99%
“…88 Other TPE interventions provided approaches that included feedback on dietary intake patterns and enhancing medication adherence. 63,73,74,87,92,94,95 The activation of selfmanagement resources (eg, environmental restructuring, eliciting support from family, cognitive restructuring, and relaxation response) 82 and the use of family-focused interventions were other strategies used in other self-management trials 60,73 to enhance mutual support, communication, and problem-solving skills…”
mentioning
confidence: 99%
“…Participation of patients in management of self-care enables independency and improves health status outcomes (Ryan & Sawin, 2009). In addition rehabilitation interventions that focus on self-management and self-care are good choice to promote HRQOL (Tung et al, 2013). RTAs survivors with functional disabilities need to learn new strategy of self-management in order to return to normal life and re-assume their social and family roles.…”
Section: Introductionmentioning
confidence: 99%